Antioxidant and Cytotoxic Activity Test of Srikaya (Annona squamosa L.) Leaves and Matoa (Pometia pinnata) Leaves Extract Combination on Oral Squamous Carcinoma Cells (HSC-3) - Izzati, Putri Arifa; Marsiati, Himmi (Jurnal Indonesia Sosial Sains, 2025)
Oral cancer, particularly oral squamous cell carcinoma, is a prevalent and lethal disease that often metastasizes to surrounding tissues. Traditional treatments such as surgery, radiotherapy, and chemotherapy present various side effects, necessitating the exploration of alternative therapies. This study aims to determine the antioxidant value of the combination of ethanol extracts of srikaya leaves (Annona squamosa L) and matoa leaves (Pometia pinnata) against HSC-3 cell cytotoxicity. The antioxidant test on the combination of ethanol extracts of srikaya leaves and matoa leaves using DPPH assay to obtain IC50. HSC-3 cell lines were treated with a combination of ethanol extracts of srikaya leaves (Annona squamosa L) and matoa leaves (Pometia pinnata) with concentrations of 12.5 µl/ml, 25 µl/ml, 50 µl/ml, 100 µl/ml, and 200 µl/ml for 24 hours and tested with the CCK-8 assay method to calculate cell viability and obtain IC(50.The results of the antioxidant test of the combination of ethanol extracts of srikaya leaves (Annona squamosa L) and matoa leaves (Pometia pinnata) in the regression analysis results, obtained a significant value of p-Value = 0.033 <0.050, so it is stated that the concentration has a significant effect on inhibition. In the results of IC 50 obtained 7.62 µl / ml shows antioxidant activity is classified as very strong which is characterized by the value of IC 50 < 50 µl / ml. Statistical analysis using ANOVA followed by Tukey's HSD post hoc test obtained (p-Value = 0.000 with a correlation value of r = 0.599) means that the treatment given does not have a significant effect on the observation results. Ethanol extracts of srikaya leaves (Annona squamosa L) and matoa leaves (Pometia pinnata) have the potential to be made as a therapy using natural ingredients on anticancer HSC-3 cancer cells.